Control of Neonatal Diarrhea in Piglets with Reduced Antibiotic Use by Application of a Complementary Feed—A Randomized Controlled Farm Trial - Klaus K. Sall; Leslie Foldager; Charlotte Delf; Sigurd J. Christensen; Michael N. Agerley; Kristian T. Havn; Carsten Pedersen (Veterinary Sciences)
The objective of this farm trial was to investigate if the consumption of antibiotics could be reduced when piglets showing early signs of neonatal diarrhea were treated with an oral dose of tannin extract derived from sweet chestnut wood. The farm had a very high incidence of neonatal diarrhea among gilt litters. Gilts were randomized into test or control groups in a 1:1 ratio to compare the consumption of antibiotics used for piglets and piglet mortality during the four-week trial period. Control litters were treated with the oral antibiotic paromomycin, while test litters were treated with the complementary feed O-Nella-Protect. The farm trial included 18 gilt litters comprising 254 piglets. In the control group, 100% of the piglets received antibiotic treatment. In the test group, consumption of antibiotics used against diarrhea was reduced by 84% (p = 0.001) and consumption of antibiotics used for other illnesses was reduced by 45% (p = 0.045). In both test and control groups, six piglets died. Microbiological analysis identified both potential bacterial and viral pathogens. In conclusion, the farm trial indicates that even under the challenge of potentially serious bacterial and viral pathogens, a complimentary feed containing a tannin extract can support piglet health and reduce antibiotic consumption.